THE JUDICIALIZATION OF ABORTION: : AND ITS DECRIMINALIZATION FROM A COMPARATIVE PERSPECTIVE - Eidelwein, Tamires; Eidelwein Silveira, Gabriel; Cavalcante Moura, Mariana; Regina Quaresma da Silva, Denise (Revista Gênero e Interdisciplinaridade, 2021)
This research addresses the issue of the judicialization of social relations and the debate on the decriminalization of abortion based on the decision drawn up by Justice Barroso, at the Brazilian Federal Supreme Court, in habeas corpus 124.306 / RJ, compared to the leading case Roe v. Wade of the United States Supreme Court. It aims to study the main intersections between the arguments adopted in the famous decision in Roe v. Wade, and those developed at Justice Barroso’s opinion, in the aforementioned habeas corpus, in which our constitutional court recognized, although for different reasons, the same right affirmed in the paradigmatic case. This is a qualitative research, carried out through a deductive method and a bibliographic and documentary technical procedure. Thus, the first notes expose the main arguments of the case Roe v. Wade of the United States Supreme Court. Next, we speculated on fundamental rights and constitutional principles mentioned by the decision drawn up by Justice Barroso in the Habeas Corpus. Finally, we seek to understand the role of constitutional courts in the face of the provocations imposed on them by social changes, issues that, a priori, would be the responsibility of other branches of the government, such as the legislative and the executive. For the interpretation of judicial decisions, we adopted the content analysis procedure, identifying the central arguments of each of the considered decisions, for later comparison, in order to reconstruct their rationality and identifying whether and in what sense they corroborate the general hypotheses about the institutional and material transformations in the democratic regime